An experimental study on the potential purchase behavior of Chinese consumers of new energy hybrid electric vehicles - Guo, Qing; Liu, Youqian; Cai, Luxin (Frontiers in Environmental Science, 2023)
The automotive industry has paid close attention to the promising future of new energy vehicles, and the new energy hybrid electric vehicles that fall under this category are gradually entering the public eye. This paper uses the SPSS software to conduct an experimental study on the “purchase preference for new energy hybrid vehicles” and its influencing factors of different types of consumers in China, based on 379 questionnaires and the results of situational experiments conducted by the research group in 24 cities across the country. The findings are as follows: 1) Different categories of consumers have a large gap in their cognitive preferences for new energy hybrid electric vehicles; 2) There is little difference in “purchase preference for new energy hybrid electric vehicles” among different categories of consumers; 3) The improvement of education and income has a significant effect on promoting consumers’ “environmental awareness”; 4) Consumers’ perception of the government’s new energization policy is positive. Based on the preceding conclusions, this paper puts forward the policy recommendations to promote new energy hybrid electric vehicles.